PENGARUH DISIPLIN, KOMPETENSI KEPRIBADIAN DAN SUPERVISI KEPALA SEKOLAH TERHADAP KINERJA GURU SMP NEGERI DI PALEMBANG - Astining Putri, Nuraida; Seri, Herman; Sakdiahwati, Sakdiahwati (Universitas muhammadiyah palembang, 2019)
The purpose of the study was to determine the effect of discipline, personality competence and supervision of the principal on the performance of the teachers of the Public Middle School in the Seberang Ulu 1 District of Palembang.The research design uses an associative type. The population in this study were teachers of Public Middle Schools in the Seberang ULU 1 Palembang District, amounting to 305 people. The sampling technique in this study is cluster sampling. The sampling technique uses the Yamane formula to obtain 173 people, the analysis model used uses multiple linear regression methods.The results showed that: 1) There was a significant effect of discipline, personality competence and supervision of principals together on the performance of teachers in the Public Middle School in the Seberang ULU 1 Palembang District. 2) There is a significant effect of discipline, personality competence and supervision of principals partially on the performance of teachers in the Public Middle School in Seberang District ULU 1 Palembang.The implications of this study provide results that principals as leaders must be able to provide examples of discipline to teachers accompanied by communication that can lead to compliance. The principal includes his teacher for personality training to improve knowledge, skills, skills, and attitudes to be able to carry out tasks and positions based on the personality needed by a teacher. Furthermore, the principal needs to master the supervision technique so that he can find out the problems that occur in his school.